Corporate Social Responsibility’s impact on the development of small and medium-sized businesses in the region: The study of the food sector of the Lviv region in Ukraine - Martyniuk, Volodymyr; Sokil, Oksana; Lančarič, Drahoslav; Tsygylyk, Natalia (<center>Conference Proceedings Determinants Of Regional Development</center>; No 2 (2021): Conference Proceedings - VIII International Scientific Conference Determinants of Regional DevelopmentDO - 10.14595/CP/02/013, 2021)
The "corporate social responsibility" (CSR) phenomenon indicates that this practice applies to large enterprises. However, the competition in markets does not know the rules. In this case, the question of the need for CSR for SMEs arises. SMEs have difficulties with CSR activities’ implementation due to limited financial and human resources. Therefore, for the study, we have chosen SMEs and their CSR experience. The purpose of the work is to find out the most important factors that influence the CSR perception of SMEs among food service enterprises in the Lviv region of Ukraine. The respondents' attitude towards activities in three main CSR pillars (ecological, economic and social areas) is researched. Representatives of executive positions of companies were the respondents within the study. A quantitative approach using questionnaires was adapted to the survey, using a sample of 107 representatives of SMEs in the foodservice sector. There was performed a statistical analysis by using IBM SPSS software and MS Excel. Regression analysis, Correlation analysis, and ANOVA were used to process and evaluate the received data. We can conclude that the research describes the main factors that motivate a company to carry out CSR activities. In addition, we have analyzed the main measures in the three pillars of CSR. The study is focused on the food service business. The document also concentrates on the work of small and medium enterprises in the context of the three main areas of CSR. This study can give impetus to new research among SMEs and their performance in the CSR direction.